Efecto de la relación pulpa - mucílago de melón amargo (momordica charantia) en la concentración final de una leche fermentada - Vera Saltos, Andrea Patricia (2019)
The objective of this investigation was to evaluate the effect of the relation of pulp and mucilage of the bitter melon (momordica charantia) in the final concentration of a fermented milk. A Completely Randomized Design was used with three replications for each treatment, taking as an experimental unit 2 L of milk per replicate evidencing that 24 liters of this raw material was needed, 135 mL of mucilage, 405 g of bitter melon pulp. The following variables were evaluated: pH, acidity, ºBrix, density, syneresis and viscosity. The results showed in the ANOVA that the variable viscosity presented significant statistical difference by means of the honestly significant Tukey test at 0.05. Regarding the microbiological analyzes in none of the treatments, there was presence of pathogenic microorganisms. It is concluded that all the relationships of bitter melon pulp and mucilage influenced the viscosity of the fermented milk (yogurt) showing that T2 (12% pulp - 3% mucilage) is what provides the characteristic for a commercial yoghurt, not so in the acceptability of the product.